Economic Innovation for Global Food Crisis: Technology-based Sustainable Solutions Review - Judijanto, Loso; Lubis, Mitra Musika; Slamet Riyadi, Slamet Riyadi; Krisprimandoyo, Denpharanto Agung; Koentjoro, Yonny (PT. Riset Press International, 2024)
One of the biggest problems confronting humanity in the twenty-first century is the global food crisis. Global food security is becoming more and more precarious as population growth picks up speed and climate change puts agricultural sustainability and food security in jeopardy. Technology is an important factor for increasing sustainable food systems in order to accomplish this goal. Smart Farming concept combines sensors, data analytics, artificial intelligence, Internet of Things (IoT), and information and communication technology (ICT). In this research paper, the researchers' method of gathering data is documentation studies. This research aims to review technologies that could be utilized to overcome the global food crisis, one of which is smart farming. The society is expected to contribute to collective efforts to create a world free of starvation and abundant food for all through this understanding of smart farming.